Beyond the Berger Inquiry: Can extractive resource development help the sustainability of Canada’s arctic communities? - Southcott, C. (Chris); Abele, F. (Frances D.); Natcher, D. (David); Parlee, B. (Brenda) (ARCTIC, 2018)
The four decades since the Berger Inquiry have produced a large body of research demonstrating the positive and negative impacts of resource development on northern communities. However, little independent research has aimed to yield an understanding of how best to manage the impacts of resource development and to harness its benefits in ways that can promote long-term sustainable development. This question was the impetus for the Resources and Sustainable Development in the Arctic (ReSDA) research project funded by the Social Sciences and Humanities Research Council of Canada in 2011. Representing a network of researchers, community members and organizations, ReSDA researchers conducted a series of analyses that focused on what was needed to ensure that northern communities received more benefits from resource development and potential negative impacts were mitigated. Overall, the analyses highlight the serious gaps that remain in our ability to ensure that resource development projects improve the sustainability of Arctic communities. These gaps include a proper understanding of cumulative impacts, the ability of communities to adequately participate in new regulatory processes, the non-economic aspects of well-being, the effects of impact and benefit agreements and new financial benefits, and new mitigation activities.